Canada’s role in the foreign aid programmes to the developping nations : a geographical appraisal - Cermakian, Jean (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1968)
This article shows first of all the importance of geographic studies of the foreign aid programmes as necessary adjuncts to the analysis of trade flows between industrial-ised and less-developed countries. Secondly, it deals briefly with the total volume of bilateral and multilateral external aid in the world and ranks Canada among the first fifteen donor countries. Finally, it emphasizes the evolution of the spatial distribution of Canada's bilateral external aid programme. Beginning as an integral part of the Colombo Plan in 1950, this programme was extended to the other Commonwealth countries in 1958 (Caribbean) and 1960 (Africa). Only in 1961 did it go beyond the Commonwealth framework due to Canada's bilingual and bicultural character (aid to French-speaking Africa) and to its location in the Western Hemisphere (aid to Latin American, beginning in 1964). The article concludes by stressing the need for further studies in this field, at a time when Canada seems to indicate willingness to intensity its external aid commitments.